Determination of progestational action of a synthetic steroid - Gonzáles Enders, Rodolfo (2015)
The pharmacological effects of the compound RH 2267, progestational drug capacity, end female genital organs are studied. The progestational effect was found at doses of 230-500-75 and 1000 mcgrs. At higher doses, induce withdrawal bleeding.